Foudroyant middle-ear pneumococcal inflammation with meningoencephalitis in a six-year-old girl - Čvorović, Ljiljana; Relić, Nenad; Rsovac, Snežana; Arsović, Nenad (Vojnosanitetski pregled, 2021)
Introduction. Intracranial complications of otitis media still occur, despite great progress in the treatment of all forms of inflammation. These are serious conditions which are still life-threatening and require a fast and accurate diagnosis and an adequate treatment. We present an illustrative case of an acute, foudroyant, pneumococcal, suppurative otitis media with infection spreading into endocranium and development of meningoencephalitis and otic hydrocephalus. Case report. A 6-year-old girl was admitted to the University Children’s Clinic in Belgrade, Serbia, because of fever, headache, vomiting and disorder of consciousness. Computed tomography scan of the endocranium and temporal bone revealed brain edema and hypodense content in the left mastoid and tympanic cavity. The diagnosis of acute otitis media with meningoencephalitis was made and we started with intensive antibiotic treatment. Lumbar puncture and hemoculture confirmed a pneumococcal infection. Otosurgical treatment was conducted, too, due to an inadequate reaction to the conservative treatment. Firstly, left mastoidectomy with the implantation of a ventilation tube was performed, followed by a radical tympanomastoidectomy, because there was no improvement. Three weeks after the second operation, a magnetic resonance imaging of the endocranium was performed and an otic hydrocephalus was diagnosed. A neurosurgical operation was performed on the same day with the setting of the ventriculoperitoneal shunt. Conclusion. Intracranial complications of acute otitis media in children are extremely rare and they require a multidisciplinary treatment. Surgical treatment of the ear should not be postponed and the choice of the type of otosurgical intervention should be individually adapted. Audiological and neurological complications of the disease are frequent and they further prolong and impair the treatment.